The Effect of Board Size and Gender Diversity on Company Performance Moderated by Political Connections and Family Ownership - Teddy Jurnali; Nada Haniyyah (Universitas Internasional Batam, 2024)
The purpose of this study was to examine the relationship between board size and board gender diversity on financial performance using political connections and family ownership as moderating variables. The research population consists of all sectors except the financial sector which is listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Purposive sampling is used in the sampling approach, using research data obtained from the company's annual report. The data analysis used in this research is panel data regression with Eviews software. The research findings show that board gender diversity has a significant effect on company performance, while company size does not affect company performance. The findings also show that political connections cannot moderate the relationship between board size and board gender diversity on firm performance, whereas family ownership can moderate the relationship between board size and board gender diversity on financial performance.